2020
DOI: 10.1016/j.asmart.2020.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hamstring autograft diameter on graft failure rate in Chinese population after anterior cruciate ligament reconstruction

Abstract: Background There has been limited literature regarding the influence of hamstring autograft diameter on the outcome of anterior cruciate ligament (ACL) reconstruction in Asian population. This study was undertaken to investigate the failure rate after ACL reconstruction among Chinese patients treated with hamstring tendon autografts of different diameters. Our hypothesis was that an increase in hamstring tendon autograft diameter would reduce the risk of graft failure. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
0
14
1
Order By: Relevance
“…Similarly, a study of 4029 patients from the Norwegian Knee Ligament Registry also found that when compared with patients with an 8-mm graft, the risk of revision was no different in patients with a 7.5-mm (adjusted HR, 0.86 [95% CI, 0.52-1.43]) or a ≤7-mm graft (adjusted HR, 0.59; [95% CI, 0.30-1.14]). 12 Other retrospective studies performed by Tang et al 41 and Kamien et al 14 found no association between revision risk and grafts <8 mm. In contrast, a study of 18,425 patients combined from the Swedish and Norwegian national knee ligament registries found a higher revision risk when comparing <8-mm to ≥8-mm grafts (adjusted relative risk [RR], 1.25; P = .047).…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, a study of 4029 patients from the Norwegian Knee Ligament Registry also found that when compared with patients with an 8-mm graft, the risk of revision was no different in patients with a 7.5-mm (adjusted HR, 0.86 [95% CI, 0.52-1.43]) or a ≤7-mm graft (adjusted HR, 0.59; [95% CI, 0.30-1.14]). 12 Other retrospective studies performed by Tang et al 41 and Kamien et al 14 found no association between revision risk and grafts <8 mm. In contrast, a study of 18,425 patients combined from the Swedish and Norwegian national knee ligament registries found a higher revision risk when comparing <8-mm to ≥8-mm grafts (adjusted relative risk [RR], 1.25; P = .047).…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, we observed that a graft of 4 mm radius leads to satisfactory responses as predicted by the model. This graft size is a common surgery choice as reported in literature 11 , 102 – 104 . Subsequently, we performed a sensitivity analysis to investigate the impact of pretension on knee laxity.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, we observed that a graft of 4 mm radius leads to satisfactory responses as predicted by the model. This graft size is a common surgery choice as reported in literature 11,[99][100][101] . Subsequently, we performed a sensitivity analysis to investigate the impact of pretension on knee laxity.…”
Section: Discussionmentioning
confidence: 98%